The PERMA+I Model as an Islamic Values-Based Positive Education Framework: An Ethnographic Study at Edufic - Alhail, Hadi; Fathiyah, Kartika Nur; Juliati, Ade Putri; Pertiwi, Sekar Ayu Fajar; Hayundaka, Anandam; Muhladin, Hildan; Almedy, Taufik Hidayat (International Journal of Islamic Educational Psychology, 2025)
This study explores how the concept of positive education is perceived and implemented by leaders and teaching staff at the non-formal educational institution Edufic. Positive education integrates the principles of positive psychology into the learning process to enhance students’ well-being, learning motivation, and academic achievement. Using a qualitative ethnographic design, data were collected through in-depth interviews and participatory observation and then analyzed using Spradley’s model, which includes semantic, domain, taxonomic, componential, and thematic analyses. Data validity was ensured through triangulation until saturation was reached. The findings revealed that positive education at Edufic is designed to develop Islamic literacy through the integration of the UK and Al-Azhar curricula, with a focus on promoting positive emotions. The concept is perceived through six main sub-domains: (1) happiness, love of learning, optimism, flow, and enthusiasm; (2) curiosity and interest; (3) support, empathy, acceptance, and appreciation; (4) purposeful and systematic behavior; (5) productivity, motivation, and success; and (6) monotheism and piety. The integration of Islamic values expands the meaning of each PERMA+I domain—Positive Emotion, Engagement, Relationship, Meaning, Accomplishment, and Islamic Value through concepts such as tawhid, akhlaq, and worship. Overall, Edufic’s system does not adopt a secular view that separates knowledge from religion; rather, it integrates Islamic values as the essence of faith and moral beauty within the PERMA model. Thus, the adaptation of the PERMA+I model bridges Western positive psychology with Islamic spirituality, creating a holistic, contextual, and transcendental framework for positive education in non-formal settings.